NEUROMUSCULAR ELECTRICAL STIMULATION EFFECT ON WRIST SPASTICITY AND FUNCTION IN POST-STROKE PATIENT WITH UPPER EXTREMITY RECOVERY EXERCISE - Setianto, Catur Ari; Syahrir, Ahmad; Ridwan, Mochammad (MNJ (Malang Neurology Journal), 2024)
Background : Stroke is still a major health problem in the world and cause disability. Spasticity is one of the disability problems in stroke patients, which is more common in the wrist muscles. Recovery of spasticity is quite difficult and there is no definitive treatment that can speed up the recovery. Electrical stimulation is one of the rehabilitation intervensions that is believed to be able to recover spasticity based on neuroplasticity theory. There has been no consensus for the method of electrical stimulation that can give rise to optimal effects in stroke patients. New studies are still needed to determine effective therapeutic programs. Objective : The study aims to determine the effectiveness of the use of Wrist Neuromuscular Electrical Stimulation (NMES) against the recovery of spasticity and functional degrees of post-stroke patients who receive upper extremity recovery exercise (URE). Methods : The study used a randomized controlled trial. The study sample was stroke patients who are treated at dr. Saiful Anwar hospital policlinic. The study involved 30 post-stroke patients who were randomized into NMES combined with URE groups (15 patients) and URE groups (15 patients). Modified Asworth Scale and Fugl-Meyer Assesment of Upper Extremity total were measured before and after interventions. Modified Asworth Scale (MAS) is a scale than use for measure spasticity degree and have very good realibility. Fugl-Meyer Assesment Scaletha (FMA) is a scale for measure fungsionality of extremities which also have good realibility. Neuromuscular Electrical Stimulation (NMES) device is BTL-5000 series. Results : NMES combined with URE can reduce the degree of spasticity and increase the functional degree of the wrist in post-stroke patients significantly (p<0.05). URE can also significantly reduce the degree of spasticity and increase the functional degree of the wrist (p<0.05). NMES compared to URE futher reduced the degree of spasticity and increased the functional degree of the wrist in post-stroke patients insignificantly (p>0.05). Conclusion : The mean decrease in the degree of spasticity and increase in functional degree in the NMES group combined with URE measured by MAS scale showing that degree of spasticity with sig 0,101 > alpha (0,05) is not significant, but the mean decrease MAS in the NMES with URE group is bigger than group URE alone. The mean decrease in the degree of spasticity and increase in functional degree in the NMES group combined with URE measured by FMA scale showing that degree of spasticity with sig 0,787 > alpha (0,05) is also not significant, but the mean decrease FMA in the NMES with URE group is bigger than URE alone. This results mean that there is a significant score decrease in spasticity and increase of fungsionality degree before and after URE grop and there is not significant different score using NMES and URE group in MAS and FMA scale.